NZ J Ecol 2016
DOI: 10.20417/nzjecol.40.14
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of biodiversity in a dryland remnant within an intensified dairy farm landscape

Abstract: Abstract:The lowland Canterbury Plains of New Zealand have been extensively modified since human occupation, but with recent conversions to irrigated dairy farming very few remnants of native dryland vegetation remain in the region. We investigated soil chemistry, plant distribution and soil invertebrates along transects in Bankside Scientific Reserve, a small (2.6 ha) remnant. The vegetation is a mosaic of native woody shrubs, predominantly Kunzea serotina (kanuka, Myrtaceae) and Discaria toumatou (matagouri,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 28 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…Native species in the Megascolecidae family are often restricted to protected habitats and remnants of native vegetation, but they are also found on the borders of agricultural land (Kim et al 2015). Coexistence of native and exotic species has recently been reported where patches of native vegetation borders agricultural land (Kim et al 2015;Bowie et al 2016) or when native vegetation is restored on agricultural land .…”
Section: Introductionmentioning
confidence: 99%
“…Native species in the Megascolecidae family are often restricted to protected habitats and remnants of native vegetation, but they are also found on the borders of agricultural land (Kim et al 2015). Coexistence of native and exotic species has recently been reported where patches of native vegetation borders agricultural land (Kim et al 2015;Bowie et al 2016) or when native vegetation is restored on agricultural land .…”
Section: Introductionmentioning
confidence: 99%
“…Human colonization and introduction of mammalian pests to these islands has been relatively recent, but native biodiversity has been impacted particularly severely (Lee, 1961;Sparling and Schipper, 2002;MacLeod and Moller, 2006). Agricultural modification of landscapes, vegetation and soils has certainly been to the detriment of native earthworms (Lee, 1959a;Molloy, 1988;Bowie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The apparent inability of endemics to survive in agricultural land has encouraged efforts to increase the dispersion of exotic earthworms in New Zealand agricultural land in recent years. At the same time, the ability of exotic earthworms to encroach under New Zealand native vegetation has only very recently been investigated (Bowie et al ). The introduction of similar European species in Australia has led to concerns regarding their potential impact on native Australian soil fauna (Baker et al ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is very little information about the potential of exotic earthworms to colonize soil under native vegetation or the potential for endemic species to recover from land conversion. In a recent study, we reported the ability of exotic earthworms to move from pasture into adjacent native vegetation particularly into areas affected by leaching of soil nutrients from agricultural land (Bowie et al ).…”
Section: Introductionmentioning
confidence: 99%